2023
DOI: 10.1002/cl2.1306
|View full text |Cite
|
Sign up to set email alerts
|

Non‐familial intergenerational interventions and their impact on social and mental wellbeing of both younger and older people—A mapping review and evidence and gap map

Abstract: Background Opportunities for social connection between generations in the UK have diminished over the last few decades because of changes in the way that we live and work. The decline in communal spaces such as libraries, youth clubs and community centres mean that there are fewer opportunities to meet and mix socially with other generations outside our own families. Increased working hours, improved technology, changes in family patterns, relationship breakdowns within families and migration are also believed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…Searches were conducted to populate the evidence gap map (Campbell, 2023 ) from which this review originates. We have set up automated search alerts in the databases listed below to identify additional relevant literature which we will use to update the map as the project progresses; any studies identified by this process will be screened for eligibility in both the map and the review.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Searches were conducted to populate the evidence gap map (Campbell, 2023 ) from which this review originates. We have set up automated search alerts in the databases listed below to identify additional relevant literature which we will use to update the map as the project progresses; any studies identified by this process will be screened for eligibility in both the map and the review.…”
Section: Methodsmentioning
confidence: 99%
“…Studies will be identified from the relevant domains of our evidence and gap map and screened against the eligibility criteria independently by two reviewers. Methods for study selection used to populate the evidence and gap map can be found in the report (Campbell, 2023 ). We will also conduct citation searching (forwards and backwards) on the included studies.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, we posit a serial mediating effect, wherein older adults’ attitudes toward younger people in a non-familial context facilitate a transition to their willingness to interact with these younger people, thereby influencing the relationship between intergenerational support and mental health. Factors such as the rapid development of technology, changes in family structure, relationship breakdowns within families, and migration are believed to be catalysts for generational segregation [ 32 ].…”
Section: Introductionmentioning
confidence: 99%